Seatbelts Save Lives, and Spines, in Motor Vehicle Accidents: A Review of the National Trauma Data Bank in the Pediatric Population. Issue 23 (1st December 2021) - Sarwahi, Vishal; Atlas, Aaron M.; Galina, Jesse; Satin, Alexander; Dowling, Thomas J.; Hasan, Sayyida; Amaral, Terry D.; Lo, Yungtai; Christopherson, Nathan; Prince, Jose
Abstract : Study Design: Database study. Objective: The purpose of this study was to use a large, nationwide database to determine prevalence of pediatric spine fractures in the United States, associated injuries, mechanisms of injury (MOI), use of safety devices, and mortality rates. Summary of Background Data: Spinal fractures account for 1% to 2% of pediatric injuries. However, they are associated with significant comorbidities and complications. Motor vehicle accidents (MVAs) are most responsible for increased incidence observed. Methods: Retrospective review of National Trauma Data Bank between 2009 and 2014 (analysis in 2019) for all vertebral fractures in patients under 18 years of age. Subanalysis included those in MVAs where protective device use data were available. Patient demographics, MOI, geographical and anatomical region of injury, concomitant musculoskeletal/organ injury, protective device usage, hospital length of stay, surgical procedures, and mortality were all analyzed. Results: A total of 34, 563 patients with 45, 430 fractured vertebrae included. Median age was 15 years. Most fractures (63.1%) occurred in patients aged 15 to 17 years, most frequent MOI was MVA (66.8%), and most common geographic location was the South (38%). Males sustained more spine fractures than females, overall (58.4% vs. 41.6%; P < 0.001) and in MVAs (54.4% vs. 45.6%; P < 0.001). Those in MVAs wearing seatbelts had lower odds of cranial (29.6% vs. 70.4%; odds ratio [OR] = 0.85, 95% confidence interval [CI]: 0.82–0.89; P < 0.001) and thoracic (30.1% vs. 69.9%; OR = 0.88, 95% CI: 0.84–0.91; P < 0.001) organ injury, multivertebral (30% vs. 70%; OR = 0.78, 95% CI: 0.73–0.83; P < 0.001) and concomitant nonvertebral fractures (30.9% vs. 69.1%; OR = 0.89, 95% CI:0.73–0.83; P < 0.001), and 21% lower odds of mortality (29.3% vs. 70.7%; OR = 0.79, 95% CI: 0.66–0.94; P = 0.009). Over 70% of drivers were not restrained during MVA, with majority of seatbelt violations incurred by males, ages 15 to 17, in the South. Conclusion: Over 60% of pediatric spinal fractures occur in children aged 15 to 17 years, coinciding with the beginning of legal driving. MVA is the most common cause and has significant association with morbidity/mortality. Nearly two- thirds pediatric spinal fractures sustained in MVAs occurred without seatbelts. Absence of seatbelts associated with >20% greater odds of mortality. Ensuring new drivers wear protective devices can greatly reduce morbidity/ mortality associated with MVA. Level of Evidence: 3